UDI FENOMENOLOGI TERHADAP PRILAKU BULLYING DI SEKOLAH DASAR DAN UPAYA PENCEGAHANNYA MELALUI PENANAMAN NILAI-NILAI PANCASILA - Surul, Rofiatus; Shaleh, Shaleh (Indonesian Journal of Islamic Elementary Education, 2024)
Bullying behavior is a widespread phenomenon, including in elementary schools. This behavior has serious implications that have a negative impact on the victim, perpetrator, and even the school environment. In this context, it is important to study bullying behavior in elementary schools and design prevention efforts. Researchers use a qualitative phenomenological approach to explore how this behavior occurs, then follow up by developing prevention efforts. Data collection was carried out using observation, interviews and documentation techniques. The data that has been collected is checked for validity using triangulation techniques. The results of this research reveal that: first, there are several bullying behaviors that occur in elementary schools, namely: in the form of verbal and non-verbal bullying, verbally in the form of insulting peers based on the physical factors of friends who are different from other friends, calling friends by people's names. old and so on. Meanwhile, non-verbally in the form of pinching peers or cornering peers who are considered different. Second, efforts to overcome and prevent bullying behavior in elementary school students can be done by instilling character education values ​​in the principles of Pancasila through learning, habituation, art, and giving awards by educators to students.